2018
DOI: 10.1002/alr.22150
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive factors for additional opioid prescription after endoscopic sinus surgery

Abstract: A need for extension of postoperative opioid pain control is not uncommon after ESS. Patient baseline clinical characteristics are predictive of a need for re-prescription of opioids. Surgical extent is not associated with need for prolonged postoperative opioid pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
3
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 26 publications
2
38
3
1
Order By: Relevance
“…This does not come as a surprise considering septoplasty often requires a separate incision along with disruption of septal bone and cartilage. However, Jafari et al found that concomitant septoplasty with FESS did not increase the incidence of opioid refill requests . One possible explanation for the discrepancy compared to our findings is that the aforementioned study reported the number of refills, whereas we specifically looked at the number of tablets consumed.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This does not come as a surprise considering septoplasty often requires a separate incision along with disruption of septal bone and cartilage. However, Jafari et al found that concomitant septoplasty with FESS did not increase the incidence of opioid refill requests . One possible explanation for the discrepancy compared to our findings is that the aforementioned study reported the number of refills, whereas we specifically looked at the number of tablets consumed.…”
Section: Discussioncontrasting
confidence: 95%
“…Recent studies have advocated for restraint in opioid prescription practices following sinus surgery. For example, Jafari et al found no differences in opioid requirements in patients who underwent extended sinus procedures compared to those who did not . A study surveying the postoperative course following FESS in 46 patients found that 63% of these patients completely ceased narcotic medication usage by postoperative day 7.…”
Section: Introductionmentioning
confidence: 99%
“…However, a wide range of methods, statistical analyses, and patient populations were utilized in those studies. Some of the studies looked at categorical use of opioids (no tablets used vs more than one tablet used, refills vs none); others assessed smaller cohort sizes, which could have potentially missed significant differences, or heterogeneous groups, where, for example, patients who underwent septoplasty with turbinoplasty and those who underwent septoplasty without turbinoplasty were included in the same group . Nevertheless, there is much to gain by looking at the similarities and differences in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 4.1% of patients received an opioid prescription refill within 2 weeks after ESS. A prior study of 121 patients found that 18% of patients received an additional prescription within 60 days of ESS . Annually, 500 hospital revisits are estimated to be due to inadequate pain control after ESS, which results in significant burden for the health system and to patients .…”
Section: Discussionmentioning
confidence: 99%
“…A prior study of 121 patients found that 18% of patients received an additional prescription within 60 days of ESS. 16 Annually, 500 hospital revisits are estimated to be due to inadequate pain control after ESS, which results in significant burden for the health system and to patients. 17 Accurately predicting postoperative analgesic requirements is therefore essential for the overall success of a new postoperative pain control strategy for our specialty.…”
Section: Discussionmentioning
confidence: 99%